Fish Performance Indicators Adjacent to Oil Sands Activity: Response in Performance Indicators of Slimy Sculpin in the Steepbank River, Alberta, Adjacent to Oil Sands Mining Activity. (30th December 2019) - Tetreault, Gerald R.; Bennett, Charles J.; Clark, Thomas W.; Keith, Heather; Parrott, Joanne L.; McMaster, Mark E.
Abstract: Since 2009, the Canadian and Alberta governments have been developing monitoring plans for surface water quality and quantity of the lower Athabasca River and its tributaries (2010–2013). The objectives of the present study to the fish monitoring program were to 1) assess the current status of fish in a tributary of the lower Athabasca River, 2) identify existing differences between upstream reference and within the oil sands deposit exposure sites, and 3) identify trends/changes in fish performance indicators relative to historical studies. The present study examines the fish performance indicators in slimy sculpin ( Cottus cognatus ) in the Steepbank River, Alberta, in terms of growth, gonad size, condition, and hepatic 7‐ethoxyresorufin‐ O ‐deethylase (EROD) activity as an indicator of exposure to oil‐sands‐related compounds. The sampling program followed historical sampling methods (1999–2000) to provide comparable data over time with an additional upstream site ( n  = 2) added as development progressed. Consistent changes were documented in sculpin collected from downstream sections of the Steepbank River within the oil sands deposit ( n  = 2) in 2010 through 2013. Sculpin demonstrated increased liver size with corresponding induction of EROD activity consistent with historical data and reductions in energy investment relative to reproductive development and gonadal steroid production capacity. There was no consistent evidence of changes in fish performance indicators with increased surface mining development, particularly adjacent to the Steepbank River Mid site. Although physical development in the Steepbank watershed has increased over the last 15 yr, these results are consistent with historical data suggesting that the magnitude of the response in the aquatic environment adjacent to the development has not changed. Environ Toxicol Chem 2020;39:396–409. © 2019 SETAC